VARIATION OF CARBON SOURCES IN PRODUCTING RHAMNOLIPID BY Pseudomonas aeruginosa FOR MICROBIAL ENHANCED OIL RECOVER’S APPLICATION (VARIASI SUMBER KARBON PADA PRODUKSI RHAMNOLIPID OLEH Pseudomonas aeruginosa DALAM APLIKASI MICROBIAL ENHANCED OIL RECOVERY (MEOR)) - Nafian Awaludin; Cut Nanda Sari (Testing Center for Oil and Gas LEMIGAS, 2017)
The decrease in oil production is caused by the ageing of oil production wells. The enhanced oil recovery (EOR) technology is proven to increase oil reserves and production in mature oil fields. One EOR technology that has proven to be efficient in increasing oil production is microbial EOR by using biosurfactant. The most effective biosurfactant is rhamnolipid produced by Pseudomonas aeruginosa, the bacteria of which can lower the interfacial tension between the petroleum and water. In biosurfactant’s production thanks to these bacteria, the substrate as the source of carbon in the fermentation process is needed. The sources of carbon used in this study are glucose, glycerol, molasses, banana peels, and waste from Pseudomonas aeruginosa by using Busnell Hass medium as a liquid medium of bacterial growth. Biosurfactant’s production results are; 74mg/L from glucose; 63mg/L from banana peels; 66mg / L from glycerol; 85mg/L from waste cooking oil; and 64mg/L of molasses with the following decreasing surface tension: 33.55 mN/m from glucose; 32.51 mN/m from banana peels; 27.55 mN/m from glycerol; 22.46 mN/m from waste cooking oil; and 31.49 mN/m from molasses. In addition, the decrease of interface tension of glucose; banana peels; glycerol; waste cooking oil; and molasses are as follows : 15.2 mN/m; 13.78 mN/m; 8:15 mN/m; 0.14 mN/m; and 11.2 mN/m respectively. Menurunnya produksi minyak bumi disebabkan karena sumur produksi yang sudah tua. Teknologi enhanced oil recovery (EOR) terbukti mampu meningkatkan cadangan dan produksi lapangan minyak mature. Salah satu teknologi EOR yang dikenal efi sien dalam meningkatkan perolehan minyak adalah microbial enhanced oil recovery menggunakan biosurfaktan. Biosurfaktan yang paling efektif adalah rhamnolipid yang dihasilkan oleh bakteri Pseudomonas aeruginosa yang dapat menurunkan tegangan antarmuka antara minyak bumi dengan air. Dalam produksi biosurfaktan oleh bakteri ini, diperlukan substrat sebagai sumber karbon dalam proses fermentasi. Sumber karbon yang digunakan pada penelitian ini adalah glukosa, gliserol, molase, kulit pisang, dan minyak jelantah. Penelitian ini bertujuan untuk mengetahui sumber karbon yang paling optimum dalam menghasilkan biosurfaktan dari Pseudomonas aeruginosa dengan menggunakan busnell hass medium sebagai media cair pertumbuhan bakteri. Produksi biosurfaktan yang dihasilkan adalah 74mg/L dari glukosa; 63mg/L dari kulit pisang; 66mg/L dari gliserol; 85mg/L dari minyak jelantah; dan 64mg/L dari molase dengan penurunan tegangan permukaan berturutturut: 33,55 mN/m dari glukosa; 32,51 mN/m dari kulit pisang; 27,55 mN/m dari gliserol; 22,46 mN/m dari minyak jelantah; dan 31,49 mN/m serta memiliki penurunan tegangan antarmuka dari glukosa; kulit pisang; glisero; minyak jelantah; dan molase berturut-turut adalah 15,2 mN/m; 13,78 mN/m; 8,15 mN/m; 0,14 mN/m; dan 11,2 mN/m.